Isolation of Dunaliella salina Microalgae from Pari Island, Jakarta, Indonesia - Andri Hutari; Ranti An Nisaa; Suhendra Suhendra; Husnin Nahry Yarza; Devi Anugrah (Jurnal Biologi Tropis, 2022)
Dunaliella salina is a microalga from the Chlorophyta group which is reported to be found in mangrove forests. These microalgae are reported to have economic value as a producer of beta carotene, astaxanthin, and EPA fatty acids. The microalga was isolated from Pari Island, Jakarta. Sampling by streak plate method. This study aimed to obtain Dunaliella salina isolates for further exploration. The results obtained were, that three pure isolates MKA1, MKA2, and MKA3, were successfully purified. The three isolates showed oval-ovoid morphology and orange-pink pigmentation of the culture. Cultivation using seawater, glucose (10 g/L) and yeast extract (3 g/L) produced biomass of about 2.3 g/L and further optimization needs to be explored.